Pseudo-Second-Order Kinetics of Ultrasound-Assisted Antioxidant Extraction from Mangosteen Peel Using a NaDES–VCO–Ethanol Solvent (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Mangosteen peel is a rich source of xanthones and polyphenols with high antioxidant potential, but their efficient recovery requires extraction systems that are both effective and environmentally sustainable. In this study, ultrasound-assisted extraction (UAE) was combined with a hybrid green solvent consisting of natural deep eutectic solvents (NaDES), virgin coconut oil, and ethanol (VCO:EtOH = 1:1). A full 3 × 3 × 3 factorial design (27 runs) was used to evaluate the effects of NaDES concentration (30–50%), temperature (30–50 °C), and ultrasound amplitude (60–100%) on extraction yield and antioxidant activity measured by DPPH inhibition. Extraction kinetics were fitted using a nonlinear pseudo-second-order (PSO) model. The highest 60-min extraction yield was obtained at 50% NaDES, 50 °C, and 100% amplitude, reaching 26.2 ± 0.4% (n = 3), with DPPH inhibition of 94.4 ± 0.8% (n = 3). Under the same condition, the PSO model estimated an equilibrium yield (qₑ) of 26.78%, with an RMSE of 0.067. Across all treatments, RMSE values ranged from 0.011 to 0.688, and extraction yield generally approached a plateau within 45–60 min. Yield was strongly and positively correlated with antioxidant activity (r = 0.876; 95% CI: 0.79–0.93; p < 0.01). These findings show that integrating UAE, a NaDES-based hybrid solvent, and PSO kinetic modeling can improve extraction efficiency and antioxidant performance while providing a reproducible framework for mangosteen peel valorization in nutraceutical and functional-food applications.